Psychological Effects Of Music On Physical Exercise Performance - Jiangang, Wang (Journal of Neonatal Surgery, 2025)
Introduction: Over the years, music has been used as a motivating factor by human beings across different environments such as when working, having a good time, celebrating occasions, honoring soldiers, motivating and encouraging individuals, inspiring, and giving them the strength to continue [1]. This shows that the positive impact of music on individuals in sports and exercises has continued to attract more interest in research. Objectives: The objective of this study was to analyze the psychological effects of music on physical exercise. Other objectives include; to find out the general exercise response to aerobics while listening to music, to understand the psychological effects of music on physical exercises, to find out the physiological impact of music on an individual while doing aerobics and to find out the psychological effects of anaerobic and sprint. Methods: The methodology applied on the study is literature review where several researched articles on music and aerobics or physical performance were analyzed and discussed. The selection criteria included articles published in English and article that were not older than 5 years. Results: The study results indicated that music listening during exercise and sport can yield substantial positive effects for exercisers and athletes, particularly regarding enhanced emotional responses and improved physical performance, as well as reduced perceived exertion and more efficient oxygen utilization. Such repercussions are not necessarily inevitable. Conclusion: The study concludes that music can enhance both physiological efficiency and physical performance, which could be significantly beneficial for both individual and professional athletes engaged in activities where the distinctions between success and failure are exceedingly narrow.